Computer Aided Diagnosis of Bone Lesions in the Facial Skeleton - Sorgel, Wolfgang; Girod, Sabine; Szummer, Martin; Girod, Bernd (Workshop Bildverarbeitung für die Medizin, 1998)
We present a system for computer aided diagnosis of bone tumors in the facial skeleton. There are many different lesions with radiographic manifestation in the jaws. Our system helps performing the differential diagnosis of these. The input is a digitized orthopantomograph (OPG) in which the user marks the position of the lesion with a single mouse click. An active contour model then automatically finds the boundaries of the lesion. Graylevel histograms, MRSAR texture features and Gabor filter features are computed for the lesion region. These features are then combined and used to query a database containing expert-diagnosed reference cases. The result is a number of similar cases, with tumor position marked and with available expert annotations. We show good agreement between our results and differential diagnosis given by humans. The system is also a suitable tool for training and education.